Anonymous job applications and hiring discrimination - Ulf Rinne (IZA World of Labor, 2018)
The use of anonymous job applications (or blind recruitment) to combat hiring discrimination is gaining attention and interest. Results from field experiments and pilot projects in European countries (France, Germany, the Netherlands, and Sweden are considered here), Canada, and Australia shed light on their potential to reduce some of the discriminatory barriers to hiring for minority and other disadvantaged groups. But although this approach can achieve its primary aims, there are also important cautions to consider.
Keywords: J71; J78; M51; 330; discrimination; hiring; job applications; recruitment